Pengaruh Ukuran Perusahaan, Profitabilitas, Likuiditas, Kualitas Auditor dan Pertumbuhan Perusahaan terhadap Opini Audit Going Concern (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2015-2019) - Anggraeni, Novi Iswa; Nugroho, Wawan Sadtyo (Universitas Muhammadiyah Magelang, 2021)
This study aims to examine the influence of Company Size, Profitability, Liquidity, Quality of Auditor, and Company Growth on Going Concern Audit Opinions. This study uses a sample of manufacturing companies listed on the Indonesia Stock Exchange (BEI) 2015-2019. The data in this study are secondary data. The number of samples in this study were 21 companies (105 samples). Determination of the sample obtained by using purposive sampling. Hypothesis testing is done using logistic regression analysis. The results showed that company size had a negative effect on going concern audit opinion acceptance, while profitability, liquidity, auditor quality, and company growth had no effect on going concern audit opinion acceptance.